Mass Drug Administration (MDA) for Elimination of Lymphatic Filariasis: Experiences from Nayagarh District of Odisha, India - Bhatia, Vikas; Giri, Prajna Paramita; Sahoo, Soumya Swaroop; PS, Preeti; Sahu, Dinesh Prasad (Indian Journal of Community Health, 2018)
Background: India has adopted MDA strategy for elimination of lymphatic filariasis since 2004. It requires constant efforts on a nationwide scale particularly in the endemic areas for interruption of transmission of this neglected tropical disease. Aims & Objectives: This study aims to assess the coverage and compliance along with factors affecting compliance regarding MDA implementation in Nayagarh district of Odisha. Material & Methods: A cross-sectional descriptive study was conducted in November 2016 for evaluation of filariasis elimination activities carried out in the district. A pre-designed, pre-tested semi-structured interview schedule as per National Vector Borne Disease control Programme (NVBDCP) guidelines was used. A qualitative component was added to determine the perceptions and attitudes of the study population regarding MDA implementation. Data was analysed using simple proportion and percentages. Results: A total 120 households (90 rural and 30 urban) were surveyed, covering a population of 590. Overall coverage rate of study population was found to be 91.47%. The effective coverage rate was 71.1% (77.8% in rural areas and 48.8% in urban areas). The overall coverage compliance gap was 22.2, being higher in urban than rural areas. Conclusion: There is a felt need for health education activities to increase acceptance among the population coupled with supervised on the spot consumption of DEC for decreasing the coverage compliance gap. The issues regarding compliance need to be addressed for realizing the global target of eliminating lymphatic filariasis by 2020.